2014
DOI: 10.1007/s00572-014-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal fungal diversity and community composition in a lithophytic and epiphytic orchid

Abstract: Some orchid species are present as epiphytes and lithophytes in the same habitat, but little is known about the differences of their mycorrhizal fungal communities. We used Coelogyne viscosa, which occurs both as an epiphyte and a lithophyte, as a study system to investigate orchid mycorrhizal fungal communities in lithophytes and epiphytes in Xishuangbanna National Nature Reserve (Yunnan Province, China). Twenty-three fungal operational taxonomic units (OTUs) from 18 sampling sites were identified. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Ninety-six clones were randomly selected from each library and sequenced using the M13 forward primer. Our previous studies have shown that this was a large enough clonal pool for assessing total species diversity and sequencing completeness (Xing et al 2015(Xing et al , 2017. All clones were sequenced by GENEWIZ Inc., Beijing, China.…”
Section: Assessment Of Mycorrhizal Communitiesmentioning
confidence: 99%
“…Ninety-six clones were randomly selected from each library and sequenced using the M13 forward primer. Our previous studies have shown that this was a large enough clonal pool for assessing total species diversity and sequencing completeness (Xing et al 2015(Xing et al , 2017. All clones were sequenced by GENEWIZ Inc., Beijing, China.…”
Section: Assessment Of Mycorrhizal Communitiesmentioning
confidence: 99%
“…A previous study has reported OMF have highly modular architecture, reflecting an ecological barrier between epiphytic and terrestrial subnetworks on a paleotropic island ( Martos et al., 2012 ). Other studies have also reported OMF specificities (mostly Sebacinales and Tulasnellaceae), differing between terrestrial, epiphytic, and lithophytic habitats ( Oja et al., 2015 ; Těšitelová et al., 2015 ; Xing et al., 2015 , 2019 ). Because studies on the relationships among OMF compositions and orchid life forms were all conducted in tropical areas, it remains unclear if individual epiphytic and lithophytic orchids harbor different OMF at higher elevations.…”
Section: Introductionmentioning
confidence: 95%
“…Coelogyne orchids can be both epiphytic and lithophytic at the same site and are always colonized by mycorrhizal fungi. Some Coelogyne species have therefore been studied to assess correlations of OMF composition and life form ( Xing et al., 2015 , 2019 ). Many Coelogyne species are also of high ornamental value, and wild populations of this genus have been threatened by over-collection and habitat destruction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations